Fire-retardant, self-extinguishing inorganic/polymer composite memory foams - Chatterjee, Soumyajyoti; Shanmuganathan, Kadhiravan; Kumaraswamy, Guruswamy (ACS Applied Materials & Interfaces, 2017)
Polymeric foams used in furniture and automotive and aircraft seating applications rely on the incorporation of environmentally hazardous fire-retardant additives to meet fire safety norms. This has occasioned significant interest in novel approaches to the elimination of fire-retardant additives. Foams based on polymer nano composites or based on fire-retardant coatings show compromised mechanical performance and require additional processing steps. Here, we demonstrate a one-step preparation of a fire-retardant ice-templated inorganic/polymer hybrid that does not incorporate fire-retardant additives. The hybrid foams exhibit excellent mechanical properties. They are elastic to large compressional strain, despite the high inorganic content. They also exhibit tunable mechanical recovery, including viscoelastic "memory". These hybrid foams are prepared using ice-templating that relies on a green solvent, water, porogen. Because these foams are predominantly comprised of inorganic components, they exhibit exceptional fire retardance in torch burn tests and are self-extinguishing. After being subjected to a flame, the foam retains its porous structure and does not drip or collapse. In micro-combustion calorimetry, the hybrid foams show a peak heat release rate that is only 25% that of a commercial fire-retardant polyurethanes. Finally, we demonstrate that we can use ice-templating to prepare hybrid foams with different inorganic colloids, including cheap commercial materials. We also demonstrate that ice-templating is amenable to scale up, without loss of mechanical performance or fire-retardant properties.

Fluorinated nanocellulose-reinforced all-organic flexible ferroelectric nanocomposites for energy generation - Ram, Farsa; Ambone, Tushar; Sharma, Aakash; Murugesan, Rajarathinam; Kajale, Deepak; Borkar, Vivek; Ali, Shaikh Faruque; Balu, Praveen Kumar; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Journal of Physical Chemistry C, 2018)
We report here enhanced ferroelectric crystal formation and energy generation properties of polyvinylidene fluoride (PVDF) in the presence of surface-modified crystalline nanocellulose. Incorporation of only 2-5 wt % fluorinated nanocellulose (FNC) in PVDF has been found to significantly induce polar beta/gamma-phase crystallization as compared to the addition of unmodified nanocellulose (carboxylated nanocellulose). A device made up of electrically poled PVDF/FNC composite films yielded 2 orders of magnitude higher voltage output than neat PVDF in vibrational energy harvesting. This remarkable increase in energy generation properties of PVDF at such a low loading of an organic natural biopolymer could be attributed to the tailored surface chemistry of nanocellulose, facilitating strong interfacial interactions between PVDF and FNC. Interestingly, energy harvesting devices fabricated from PVDF/FNC nanocomposites charged a 4.7 mu F capacitor at significantly faster rate and the accumulated voltage on capacitor was 3.8 times greater than neat PVDF. The fact that PVDF/FNC nanocomposites still retain a strain at break of 10-15% and can charge a capacitor in few seconds suggests potential use of these nanocomposites as flexible energy harvesting materials at large strain conditions.